4-(4-Nitrobenzyl)pyridinium 3-carboxy-4-hydroxybenzenesulfonate - Smith, Graham (International Union of Crystallography, 2013)
In the title salt, C(12)H(11)N(2)O(2) (+)·C(7)H(5)O(6)S(−), the dihedral angle between the benzene and pyridine rings in the 4-(4-nitrobenzyl)pyridinium cation is 82.7 (2)°. Within the anion there is an intramolecular hydroxy-O—H⋯O(carboxylic acid) bond. In the crystal, the cation forms a single N(+)—H⋯O(sulfonate) hydrogen bond with the anion. These cation–anion pairs interact through duplex anion carboxylic acid O—H⋯O(sulfonate) hydrogen bonds, giving a centrosymmetric cyclic association [graph set R (2) (2)(16)]. The crystals studied were non-merohedrally twinned.